Influence of the instrumentation technique and apical preparation diameter on calcium hydroxide filling in simulated curved canals - Fabiana Vieira Vier-Pelisser; Ariane Meng; Letícia Caroline Benedete Netto; Marcus Vinícius Reis Só (Wolters Kluwer Medknow Publications, 2012)
Objective: This study evaluated the influence of the instrumentation technique and apical preparation size on the filling capacity of a calcium hydroxide (CH)-based paste. Materials and Methods: Fifty simulated curved canals were prepared in acrylic blocks (five groups; n = 10 each). In three groups, the canals were preflared with Gates-Glidden drills and the apical stop was prepared with #25, 30 or 35 Flexofile files. In the other two groups, the canals were prepared with ProTaper rotary instruments and the apical stop was prepared with F1 and F2. A CH paste was injected into the canals using a special syringe. The four sides of the blocks were scanned with the root curvature to the mesial, buccal, distal and palatal faces. The amount (%) of filling in the total canal area and in the apical 5 mm was obtained [analysis of variance (ANOVA); Tukey's test; α = 0.05]. Qualitative analysis of apical filling was done (absence vs. presence of filling deficiencies) (chi-square test; α = 0.05). Results: There was no significant difference in canal filling among the groups at any block side. Presence of voids was associated with the simulated mesial and distal faces. Conclusions: An effective canal filling with the CH paste was not achieved in all cases. Canal filling failure occurred mostly in the apical third. Filling deficiencies can be better visualized in canals with mesial and distal root curvatures.